Factors Affecting Intellectual Security of the People of Yemeni Society and Their Educational Controls: An Analytical Study (The Scientific Journal of University of Saba Region, 2022)
The research aimed to detect the factors affecting intellectual security of the people of Yemeni society and identify their educational controls. For achieving these aims, the research relied on the descriptive, analytical and inductive methodology by referring to primary and secondary sources related to the topic of the research in order to devise factors affecting intellectual security and their educational controls. The research concluded with a set of results. There is a group of interrelated factors that contribute to the negative impact on intellectual security of the people of Yemeni society. They are as follows: intellectual, social, political, economical and technological factors. The results also indicated that there is a system of educational controls that contribute to reducing the factors affecting intellectual security. In the light of these results, the research suggested a set of recommendations for facing the factors affecting intellectual security of the people of Yemeni society.
Keywords: factors; intellectual security; educational controls